The economic integration of immigrants in the United States: Lessons for policy - George J. Borjas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
The most important economic feature of immigration to the United States in the post- 1965 period has been a significant deterioration in the economic performance of successive immigrant waves. The policy reaction to this trend would obviously differ if the entry wage disadvantage disappeared quickly, as the immigrants assimilated in the American economy and acquired skills and information valuable in the American labour market. This paper examines the determinants of economic assimilation, and discusses how the experience of earlier immigrant waves can provide valuable information about the assimilation process the new immigrants will likely experience.
Keywords: J10; J61; 330; immigration; assimilation; economic integration; Einwanderung; Soziale Integration; USA; Migranten